2012
DOI: 10.1682/jrrd.2011.08.0141
|View full text |Cite
|
Sign up to set email alerts
|

Activity monitor accuracy in persons using canes

Abstract: Abstract-TheStepWatch activity monitor has not been validated on multiple indoor and outdoor surfaces in a population using ambulation aids. The aims of this technical report are to report on strategies to configure the StepWatch activity monitor on subjects using a cane and to report the accuracy of both leg-mounted and cane-mounted StepWatch devices on people ambulating over different surfaces while using a cane. Sixteen subjects aged 67 to 85 yr (mean 75.6) who regularly use a cane for ambulation participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As many individuals who seek physical rehabilitation walk at slower speeds, this poses a major barrier for accurate, objective monitoring. In contrast to the consumer-grade devices, commercially-available, research-grade sensors such as the Step Activity Monitor (Modus Inc., Edmonds, WA, USA) have demonstrated strong reliability and accuracy across varied levels of abilities, including differing medical diagnosis, variable gait speeds, and use of assistive devices [ 41 , 49 , 50 , 51 , 52 , 53 , 54 ] with limited data across differing environmental conditions [ 40 , 54 , 55 , 56 ]. Though this research grade device is accurate and reliable in individuals with physical impairments, the device may lack key features that would be essential for widespread clinical adoption (see Section 4 below).…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%
“…As many individuals who seek physical rehabilitation walk at slower speeds, this poses a major barrier for accurate, objective monitoring. In contrast to the consumer-grade devices, commercially-available, research-grade sensors such as the Step Activity Monitor (Modus Inc., Edmonds, WA, USA) have demonstrated strong reliability and accuracy across varied levels of abilities, including differing medical diagnosis, variable gait speeds, and use of assistive devices [ 41 , 49 , 50 , 51 , 52 , 53 , 54 ] with limited data across differing environmental conditions [ 40 , 54 , 55 , 56 ]. Though this research grade device is accurate and reliable in individuals with physical impairments, the device may lack key features that would be essential for widespread clinical adoption (see Section 4 below).…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%
“…To clarify the effects of BWS with assistive devices on locomotive physical activities, subjects with or without assistive devices should walk at the same speed. Other reports also examined the accuracy of pedometers and accelerometers in older adults, including cane users; however, these reports did not focus solely on the effects of BWS with assistive devices 14 , 15 , 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, locomotive physical activities have been objectively assessed using triaxial accelerometers 5 , 6 , 7 , 8 , 9 , 10 ) . Triaxial accelerometers have shown reliability and validity in evaluating locomotive physical activities in adults 11 , 12 , 13 ) ; however, several studies have reported inconsistent results 14 , 15 , 16 , 17 , 18 , 19 ) . Furthermore, only a few studies have examined the effects of BWS with assistive devices on predicted locomotive physical activities using a triaxial accelerometer 19 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The StepWatch 3 Activity Monitor is a medical device and validated in a lower limb amputee populations 11 and populations that include slow and/or abnormal walkers. 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 It measures not only daily steps but also peak performance index, walking distance, cadence, and cadence variability, as well as giving a functional-level assessment based on a proprietary algorithm that attempts to combine all of the metrics into one number to approximate the K-level (given as an number from 1 to 4). The functional-level algorithm was previously demonstrated to have good ( R 2 =0.78) 40 to excellent ( r =0.96) 2 agreement with clinically determined K-levels in cohorts of transtibial amputees.…”
mentioning
confidence: 99%